Efficacy of Exserohilum monoceras, a potential fungi for biocontrol of Echinochloa spesies - Sadi, Tosiah; Kadir, Jugah; Meon, Sariah; Juraimi, Abdul Shukor; Sastroutomo, Soetikno Slamet (Malaysian Agricultural Research and Development Institute (MARDI), 2011)
Indigenous Exserohilum monoceras isolate 1125 was evaluated for its efficacy on different Echinochloa species. Exserohilum monoceras spores, prepared at 103, 104, 105, 106 and 107 spores/ml concentrations and sprayed onto E. crus-galli, showed increased infectivity with increasing spore concentration. Disease progress of E. crus-galli at various leaf development stages revealed the highest area under the disease progress curve (AUDPC) was at the 4-leaf stage (535.69 unit2), followed by the 3-leaf (446.75 unit2), 2-leaf (377.22 unit2) and 6-leaf stage (263.72 unit2). The fungus was also tested on 4 species of Echinochloa. The results showed that the AUDPC was highest for E. crus- galli var formosensis (693.33 unit2), followed by E. crus-galli var crus-galli (638.33 unit2), E. oryzicola (470 unit2) and E. colona (447 unit2). The study illustrated that E. monoceras is a potential fungus for biological control that can be further developed into bioherbicide.